Methods of Thinking and Argument in SWOT Analysis - Neliwati Neliwati; Kenny Agusto Arie Wibowo; Aswan Aswan (Edumaspul: Jurnal Pendidikan, 2022)
Thinking is a function of the soul that contains a broad understanding, because it contains the intent and purpose to solve problems so as to find relationships and determine the relationship between one problem and another. This research is based on knowing the importance of SWOT analysis in thinking and providing good arguments. The research method used is library research. the results show: Thinking is an activity to solve problems and processes in the use of ideas or symbols, ideas and concepts both invisible and semi-visible, Argumentation as an opinion that is put forward and used to overcome a problem that is built or supported by 4 components in arguing, namely the components of claim, evidence, reasoning, and rebuttal. And SWOT analysis is a form of descriptive analysis of situations and conditions (gives an overview), which is then grouped according to their respective contributions. Its role is very important in improving the quality of education because the analysis and description provided is a benchmark in developing further educational institutions/units.